2019
DOI: 10.1177/2050312118822440
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of population screening tests to establish a healthy ageing trajectory

Abstract: Objectives:There are no agreed comprehensive tests for age-related changes to physical, emotional, mental and social functioning. Research into declining function focuses on those 75 years and older and little is known about age-related changes in younger people. The aims of this project were (1) to ascertain a comprehensive test battery that could underpin community-based health screening programmes for people aged 40–75 years and pilot both (2) community-based recruitment and (3) the utility, acceptability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Data were collected at each site for 4-6 weeks between January 2017 and June 2018 using a similar approach to the biennial Tokyo Metropolitan Institute of Gerontology healthy aging survey [30]. The development of the assessment protocol [31] and the method of data collection [32] for this study have been reported elsewhere. A summary is provided here for the convenience of the reader.…”
Section: Recruitmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Data were collected at each site for 4-6 weeks between January 2017 and June 2018 using a similar approach to the biennial Tokyo Metropolitan Institute of Gerontology healthy aging survey [30]. The development of the assessment protocol [31] and the method of data collection [32] for this study have been reported elsewhere. A summary is provided here for the convenience of the reader.…”
Section: Recruitmentmentioning
confidence: 99%
“…Data was collected between January 2017 and July 2018 on an extensive range of evidence-based health and frailty measures. These measures were identified from an extensive review of measures related to functional decline [31]. Self-reported data was collected via online or hard copy survey prior to objective assessment and included: demographic data (age; gender; ethnicity; main language spoken at home; marital status; housing; employment; income; highest level of education; diagnosed health conditions; health concerns; alcohol and tobacco use; current medications; hospitalisations, emergency department presentations, falls and 'near-miss' falls in the past 6 months; unintended weight loss; appetite; participation in community activities); and continence [33], sleep quality [34], nutrition [35], hydration, usual activity patterns [36] and psychological distress using validated instruments [37] (see Table 1).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also found positive results regarding the use of elastic devices in resistance training protocols in different scenarios [18,[30][31][32]. This fact enhances the possibilities of its use in clinical and scientific contexts, in healthy and sick populations [33][34][35].…”
Section: Discussionmentioning
confidence: 90%